Cost-effectiveness analysis of the Assessment of Burden of Chronic Conditions (ABCC) tool in primary care in the Netherlands - Manuela A Joore; Esther A Boudewijns; Mascha Twellaar; Onno CP van Schayck; Merel L Kimman; Loraine HL Peters; Annerika HM Gidding-Slok; Lotte CEM Keijsers; Jean WM Muris (BMJ Open)
Objectives The increasing prevalence of chronic conditions and multimorbidity places a significant burden on patients and leads to increasing challenges for healthcare systems, especially in primary care. Recognising the multifaceted nature of chronic conditions, the Assessment of Burden of Chronic Conditions (ABCC) tool was developed to support person-centred care, by facilitating shared decision-making and self-management. This study aims to evaluate the cost-effectiveness of the ABCC tool in primary care.Design and setting This cost-effectiveness analysis was conducted over 18 months alongside a clustered, two-arm quasi-experimental study in primary care in the Netherlands.Participants The study included 231 participants diagnosed with chronic obstructive pulmonary disease (COPD), asthma, type 2 diabetes mellitus (T2DM) and/or chronic heart failure (CHF). Of these, 173 were assigned to the intervention group and 58 to the control group.Interventions The intervention group was intended to incorporate the ABCC tool into routine consultations, while the control group had to continue care as usual.Outcome measures Outcomes were assessed from a societal perspective, including quality-adjusted life years (QALYs) derived via the EuroQol-5D-5L (EQ-5D-5L) questionnaire. Costs were measured using adapted versions of the Productivity Costs Questionnaire (PCQ) and Medical Consumption Questionnaire (MCQ). Sensitivity analyses (SAs) included a healthcare perspective, per-protocol analysis (to account for disruptions caused by COVID-19) and exclusion of home care costs (to address extreme outliers). Moreover, all analyses were performed for well-being-adjusted life years (WALYs), derived from the ICEpop CAPability measure for Adults (ICECAP-A) questionnaire.Results The ABCC tool was more expensive and effective than usual care, with an incremental cost-effectiveness ratio (ICER) of €64 525 per QALY and a 29% probability of cost-effectiveness. With the exception of the healthcare perspective, the SAs yielded more favourable outcomes in terms of cost-effectiveness, with ICERs (probability of cost-effectiveness) of €41 484 (31%), €8683 (58%) and €23 905 (48%) for a healthcare perspective, per-protocol analysis and exclusion of home care costs, respectively. Outcomes for QALY and WALY were comparable.Conclusion While the primary analysis suggested a relatively low probability of cost-effectiveness, the SAs showed higher probabilities. The per-protocol analysis suggested that the ABCC tool can be cost-effective when actually used.Trial registration number NCT04127383.